Impacto de la erosión costera en comunidades del Litoral Sur de la RAACN posterior a ETA e IOTA - Toruño Álvarez, Marjorie (UNAN-Managua, 2022)
This study presents the results of the analysis of the     impact of Coastal Erosion, which, for the purposes of this Article, shall be referred to as EC, following the     passage of hurricanes ETA and IOTA in 8 communities     of the southern coast of the Northern Caribbean Coast Autonomous Region, composed by Karatá and Wawa     Bar in the municipality of Puerto Cabezas; Haulover, Wautha Bar, Walpasiksa, Barra de Prinzapolka, Samil  and Ariswatla, in the municipality of Prinzapolka. The   main objective was to identify the impact levels in terms   of Coastal Erosion left by the passage of hurricanes ETA and IOTA in these communities.